2018
DOI: 10.1159/000490342
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Loss and Citrate Load in Pre-Dilution High Cut-Off-CVVHDF with Regional Citrate (18 mmol/L) and High Cut-Off CVVHD with Systemic Heparin: An in vitro Study

Abstract: Background: Convective therapies with high cut-off membranes (HCO) are usually not recommended because of theoretical excessive albumin loss. The aim of this in vitro study is to demonstrate the noninferior safety of pre-dilution hemodiafiltration with HCO (HCO-CVVHDF) with isotonic citrate anticoagulation (18 mmol/L) with respect to heparin anticoagulated hemodialysis with HCO (HCO-CVVHD) in terms of albumin removal and citrate load. Method: ­Albumin removal was compared in vitro between 3 pre-­dilution-HCO-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The loss of albumin is the most important adverse reaction to HCO membranes, although compared with HF membranes, HCO membranes have increased the removal of β2-microglobulin, and albumin loss also increases [52,53] . Our meta-analysis also suggested a more significant loss of albumin with the treatment of HCO membranes.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The loss of albumin is the most important adverse reaction to HCO membranes, although compared with HF membranes, HCO membranes have increased the removal of β2-microglobulin, and albumin loss also increases [52,53] . Our meta-analysis also suggested a more significant loss of albumin with the treatment of HCO membranes.…”
Section: Discussionmentioning
confidence: 58%
“…The loss of albumin is the most important adverse reaction to HCO membranes, although compared with HF membranes, HCO membranes have increased the removal of β2-microglobulin, and albumin loss also increases. [ 52 , 53 ] Our meta-analysis also suggested a more significant loss of albumin with the treatment of HCO membranes. However, based on the results of the subgroup analysis, we found that only the HCO membrane with the material of polyarylethersulfone showed a statistically significant difference in the loss of serum albumin.…”
Section: Discussionmentioning
confidence: 66%
“…The excess or deficient mass is described as a percentage of the mass entering the haemodiafilter (prefilter). The accuracy of the sampling process is assessed by the values obtained from the calculation of the percentage error of the mass balance [6,8]:…”
Section: Methodsmentioning
confidence: 99%
“…At these time points, urea and fluoride concentrations have been measured pre-filter (in the inflow line), post-filter (in the outflow line) and in the effluent line. The mass balance error, SA or SC and Cl were calculated using equations described in Table 2 [12].…”
Section: Methodsmentioning
confidence: 99%
“…A mass balance error below 10% was deemed acceptable, while a value below 5% was considered optimal. All inflow, outflow and effluent samples with solute mass balance errors higher than 10% were not considered for further analysis [12].…”
Section: Methodsmentioning
confidence: 99%